Optimism and its relationship with the physical and mental wellbeing of registered nurses - Shafiq, Rahila; Qamar, Khadija; Anwar , Shahida; Haider , Anam; Parveen , Shagufta; Naila (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: Nurses face health challenges like moral distress, low job satisfaction, and poor physical and mental health. Optimism, believing in positive outcomes, influences not only the quality of patient care but also enhances nurse’s health outcomes. This study aimed to determine the relationship of optimism with the physical and mental well-being of registered nurses in the Tertiary care hospitals of Rawalpindi METHODOLOGY: The study used a cross-sectional analytic design and convenience sampling. After obtaining written informed consent, questionnaires were distributed to 270 registered nurses in Rawalpindi, using Life Orientation Test-Revised for optimism, self-care questionnaire for physical wellbeing, and Warwick-Edinburgh for mental well-being. Data were analyzed using SPSS 26, with Spearman’s rank correlation applied to examine the relationship between optimism and physical and mental well-being. RESULTS: The study shows that registered nurses in Rawalpindi have moderate optimism (63.1%), moderate physical well-being (60.7%), and moderate mental well-being (64.3%), with varying levels of optimism and well-being. The Spearman’s rank correlation coefficient between optimism and physical well-being showed (r = 0.202**, p < 0.001), and optimism and mental well-being with (r = 0.478**, p < 0.001) revealed weak and moderate positive correlation respectively, both correlations were statistically significant. CONCLUSION: The study concludes that optimism is positively correlated with both physical and mental well-being among registered nurses of Rawalpindi. The study suggests that fostering optimism can enhance physical and mental health outcomes, potentially enhancing healthcare quality and efficiency.